The impacts of climate change on Southern African food systems - Thornton, Philip K.; Gosling, Amanda; Chesterman, Sabrina; Neely, Constance (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
This report forms part of an AICCRA knowledge series on Food Systems. This report builds upon the presentation on Climate Change and Agricultural Productivity in the Southern African Development Community (SADC) Region which was delivered at the Centre for Coordination of Agricultural Research and Development for Southern Africa (CCARDESA) Agricultural Symposium held on 10 June 2021. The report outlines the status quo of agriculture in the SADC region and the projected climate change scenarios and impacts on the region’s food value chains and food system as a whole. It then addresses other drivers affecting the region’s food system and how they can compound the impacts of the changing climate. A description of climate resilience and associated capacities is given and the importance of research in transitioning towards a more resilient regional food system. The report culminates in proposed actions for transforming the SADC food system.